Evaluation of clinical and laboratory findings of 147 patients with systemic lupus erythematosus: The relationship between anti-CCP and arthritis - Ekin, Ali; Ergüney Çefle, Ayşe (Journal of Surgery and Medicine, 2019)
Aim: Anti-cyclic citrullinated peptide antibodies (Anti-CCP) is considered as a novel marker in the assessment of rheumatoid disorders. Some studies have emphasized the importance of anti-CCP in indicating erosive arthropathy in Systemic Lupus Erythematosus (SLE), like Rheumatoid Arthritis (RA). These studies have reported that the chance of erosive arthritis development is significantly increased in anti-CCP-positive patients. This study aimed to investigate the relationship between anti-CCP and arthritis along with other clinical and laboratory parameters in patients with SLE. Methods: A total of 147 SLE patients who had been admitted to Kocaeli University Medical Faculty, Department of Internal Medicine, Division of Rheumatology between January 2001 and October 2015 were included in this retrospective study. SLE diagnosis was verified according to American College of Rheumatology (ACR) and/or The Systemic Lupus Erythematosus International Collaborating Clinics (SLICC) criteria. Patients whose diagnosis was not definite and not having anti-CCP were excluded. Results: Female/male ratio was found as 5.6, and the mean age was calculated as 43.9±11.85 years. The mean follow-up period was 73.3±44.97 months. Anti-CCP was found to be positive in ten patients whereas arthritis was found to be present in 100 patients. Anti-CCP was positive in seven patients with arthritis. RF (Rheumatoid Factor) was found as positive in 50 patients of whom 40 had arthritis. A relationship was found between Anti-CCP and RF. There was no relationship between anti-CCP and arthritis. Conclusions: Anti-CCP has been reported to be significantly related to arthritis and other characteristics of rheumatoid disorders, particularly RA in several studies. There are conflicting results about the relationship between anti-CCP and arthritis in patients with SLE. These conflicting results may be derived from different subtypes of anti-CCP (citrulline-dependent), different cut-off values, and characteristics of the patient population. We did not observe any relationship between the Anti-CCP and arthritis.